THE ANALYSIS OF HYDROLOGY IN KUPANG RIVER PEKALONGAN – BATANG - Anggriani, Esa; Anwar, Saihul (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
ABSTRACTKupang River administratively located in Batang Regency, as well as the District and City of Pekalongan, Central Java Province. The Kupang River irrigates the Kupang Watershed with an area are 194.87 Km2 and the river length are 67.5 km. The Kupang watershed is in the administrative area of 3 regencies and 1 city, that are Pekalongan City, then Batang, Pekalongan, and Banjarnegara districts.In general, semi-monthly rainfall ranges between 16 mm until 299 mm. The dry season go on April until September and the rainy season go on October until March.The purpose of this research is to do a calculation and analysis to get the amount of water potential with available data. In terms of quantity, the problem of water for agriculture especially on dry land, is about the water supply and distribution. Because the water supply is very dependent on the distribution of rainfall throughout the year which is very uneven even in the rainy season. Because of that reason the technology and methods that are effective, efficient, and can be applied in various regional characteristics are needed to meet water needs.Flood control is also very necessary to prevent floods that can occur at any time. Flood dischargeplancalculated using several methods that suitable. With this we can minimize the possibility of flooding and be responsive in an effort to minimize the worst possibilities when the floods take place.Keywords:(Analysis, Hydrology, Water Potential, Flood discharge)